Request Strategy In “Cinta Brontosaurus” Novel by Raditya Dika - Prapti Wigati Purwaningrum; Danang Dwi Harmoko (LPPM Universitas Bina Sarana Informatika, 2023)
The title of this research is request strategy in “Cinta Brontosaurus” novel by Raditya Dika. The purpose of this research is to find how the characters in “Cinta Brontosaurus” novel ask someone to do something or not to do something. This research is analyzed by using theory request from Trosborg. This study uses descriptive qualitative perspective. 16 data are taken from “Cinta Brontosaurus” novel. The conclusions of this research are there are three request strategies apply in utterances. Request strategy is mostly used by the characters is elliptical in request strategy 8. By using this strategy, the speaker wants to state his or her intention explicitly. Next request strategy is mild and strong hint in strategy 1. It is used to minimize the possible refusal and to soften the request. Besides that, this strategy is the important way for the speaker to get the permission and check the hearer’s ability. Not only female but also male want to minimize the possible refusal and to soften the request in a polite way.